Pembaruan Hukum Islam di Indonesia - Ismail, Ismail (Research and Development Institution, Darussalam Institute for Islamic Studies, 2019)
In the early days of the entry of Islam in Indonesia the emphasis of Islamic teachings on legal aspects was not as strong as it is now. From the historical record, Islam that developed in Indonesia in the early days was very oriented towards tasawuf. This is because Islamic tasawuf who came to the archipelago, in certain aspects